Rafting seahorses: The presence of juvenile Hippocampus patagonicus in floating debris - Luzzatto, Diego (2013)
A total of 477 juvenile Hippocampus patagonicus recorded in 80 sampling events were detected rafting on the surface during high tide at San Antonio Bay, northern Patagonia, Argentina. If rafting juveniles drift long distances beyond their original populations, they have the potential to form new populations, which may explain the wide distribution of H. patagonicus.